PROTECTIVE EFFECT OF ZINC AGAINST THE AMMONIA INDUCED OXIDATIVE STRESS IN THE RAT TESTES - T. SIVA KUMAR,; P.NEERAJA, (International Journal of Pharma and Bio Sciences, 2015)
The aim of the present study was to assess the effects of ammonium sulphate exposure on the antioxidant defence system and lipid peroxide concentration in the testes of wistar rats, as well as the examine possible protective role of zinc from the adverse effects of ammonia .The LD50 of Ammonium Sulphate and Zinc Chloride were determined, after toxicity testing evaluation. It is 91.5 mg/kg body weight for ammonium sulphate and 58 mg/kg body weight for Zinc Chloride. The selected sub lethal concentrations of ammonium sulphate and Zinc Chloride are 18.3/kg body weight 11.6mg/kg body weight respectively. These are administered through intraperitonial method to rats for one week. After one week treatment, antioxidative enzymes like Superoxide dismutase (SOD), Catalase (CAT), and Lipid peroxidation activities were estimated in testes in albino rats by using standard methods. The impact of Zinc Chloride in rat under ammonia stress is discussed.